2023
DOI: 10.3390/vaccines11030591
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Booster Shot Preserves T Cells Immune Response Based on Interferon-Gamma Release Assay in Inflammatory Bowel Disease (IBD) Patients on Anti-TNFα Treatment

Abstract: Immune-modifying treatment in inflammatory bowel disease (IBD) impairs the humoral response. The role of T lymphocytes in this setting is still unclear. This study aims to assess if a booster shot (third dose) of BNT162b2 mRNA COVID-19 vaccine enhanced the humoral response and elicited cellular immunity in IBD patients on different immuno-therapy regimens compared to healthy controls (HCs). Five months after a booster dose, serological and T-cell responses were assessed. The measurements were described using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A multicenter prospective study involving the University of Wisconsin-Madison (Madison, WI, USA) and Mayo Clinic (Jacksonville, FL, USA) demonstrated that all IBD patients who received a third SARS-CoV-2 mRNA vaccine dose exhibited a humoral immune response [ 14 ]. Additionally, another study showed that IBD patients on similar treatment regimens to those in our study were able to mount a serological response comparable to a control group following the administration of a third dose [ 15 ]. A study focusing on patients with autoinflammatory rheumatic and musculoskeletal diseases also showed an increased humoral response in the majority of participants following the administration of a third SARS-CoV-2 mRNA vaccine dose [ 16 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A multicenter prospective study involving the University of Wisconsin-Madison (Madison, WI, USA) and Mayo Clinic (Jacksonville, FL, USA) demonstrated that all IBD patients who received a third SARS-CoV-2 mRNA vaccine dose exhibited a humoral immune response [ 14 ]. Additionally, another study showed that IBD patients on similar treatment regimens to those in our study were able to mount a serological response comparable to a control group following the administration of a third dose [ 15 ]. A study focusing on patients with autoinflammatory rheumatic and musculoskeletal diseases also showed an increased humoral response in the majority of participants following the administration of a third SARS-CoV-2 mRNA vaccine dose [ 16 ].…”
Section: Discussionmentioning
confidence: 77%
“…Ultimately, our findings are consistent with other studies that have examined anti-RBD kinetics after both two and three doses of mRNA vaccination in IBD patients, as well as patients with other autoinflammatory diseases. These studies demonstrate that mRNA vaccines are safe for use in the IBD population [ 5 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this view of our metagenome, variations in the systemic virome may contribute to phenotypic variation by regulating immunophenotype rather than acting as pathogens. In several chronic, progressive immune-mediated conditions, such as IBD, it is well known that environmental factors, gut microbiota composition, genetic predisposition, and biological treatments contribute to the impaired immune response and disease evolution [112][113][114][115][116]. However, how the gut virome behaves in this condition is not yet well understood.…”
Section: Gut Virome Dysbiosis and Transcriptional State In Healthy Ho...mentioning
confidence: 99%